Influence of Posterior Tibial Slope on the Risk of Recurrence After Anterior Cruciate Ligament Reconstruction - Mikhail S. Ryazantsev; Aleksey N. Logvinov; Dmitriy O. Ilyin; Nina E. Magnitskaya; Aziz R. Zaripov; Alexander Frolov; Aleksey P. Afanasyev; Andrey V. Korolev (Travmatologiâ i Ortopediâ Rossii, 2023)
Background. Anterior cruciate ligament (ACL) graft rupture has multifactorial causes, with traumatic factors being the most prevalent. Modern literature presents conflicting data regarding the influence of the posterior tibial slope on the risk of traumatic ACL graft rupture.